ANALISIS VO2 MAX TIM FUTSAL SMA NEGERI 22 MAKASSAR - Benny Badaru; sufitriyono sufitriyono (UNIVERSITAS NEGERI MAKASSSAR, 2021)
This research generally aims to give an idea of the extent of the VO2Max ability of the futsal team at SMA Negeri 22 Makassar. The subjects of this study were 20 students from the SMA Negeri 22 Makassar team, this sample was also called the